A REVIEW: A GREEN APPROACH FOR THE SYNTHESIS OF SILVER NANOPARTICLES AND ITS ANTIBACTERIAL APPLICATIONS - Haqq, Shyla Marjorie; Chattree, Amit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â This review is based on the synthesis of silver nanoparticles (AgNPs) using a green approach which is biofabricated from various medicinal plants. AgNPs were prepared from the various parts of the plants such as the flowers, stems, leaves, and fruits. Various physiochemical characterizations were performed using the ultraviolet (UV)-visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction spectroscopy, transmission electron microscopy, and energy dispersive spectroscopy. AgNPs were also used to inhibit the growth of bacterial pathogens and were found to be effective against both the Gram-positive and Gram-negative bacteria. For the silver to have antimicrobial properties, it must be present in the ionized form. All the forms of silver-containing compounds with the observed antimicrobial properties are in one way or another source of silver ions. Although the antimicrobial properties of silver have been known, it is thought that the silver atoms bind to the thiol groups in enzymes and subsequently leads to the deactivation of enzymes. For the silver to have antimicrobial properties, it must be present in the ionized form. The study suggested that the action of the AgNPs on the microbial cells resulted into cell lysis and DNA damage. AgNPs have proved their candidature as a potential antibacterial against the multidrug-resistant microbes. The biological agents for synthesizing AgNPs cover compounds produced naturally in microbes and plants. Reaction parameters under which the AgNPs were being synthesized hold prominent impact on their size, shape, and application. Silver nanoparticle synthesis and their application are summarized and critically discussed in this review.